Investigations on Indigenous Fuller’s Earth and its Evaluation After Acid Activation - Nizami, M Sharif; Chaudhry, M Iqbal (Biological Sciences - PJSIR, 2006)
Indigenous Fuller’s earth from Dera Ghazi Khan district, Pakistan was investigated for its physical charac- teristics, specific to bleaching palm oil. Properties such as swelling index, surface area and thermal behaviour were determined. The results showed that the studied samples had the desirable large surface area, low swelling index, and consisted of illite and montmorillonite. These were then activated by giving treatment with 4 N hydrochloric acid at 100 °C for 3 h. Raw palm oil was bleached by adding 3% activated earth and the bleaching activity was determined by Lovibond tintometer. Out of the 15 replicate specimens, more than 90% red pigment was bleached in 7 samples, whereas more than 60% red pigment bleaching was noted in 12 samples. However, bleaching of the yellow pigment was not as effective as was observed in the case of red pigment.